A Novel Kv7.3 Variant in the Voltage-Sensing S4 Segment in a Family With Benign Neonatal Epilepsy: Functional Characterization and in vitro Rescue by β-Hydroxybutyrate - Miceli, Francesco; Carotenuto, Lidia; Barrese, Vincenzo; Soldovieri, Maria Virginia; Heinzen, Erin L.; Mandel, Arthur M.; Lippa, Natalie; Bier, Louise; Goldstein, David B.; Cooper, Edward C.; Cilio, Maria Roberta; Taglialatela, Maurizio; et al. (Frontiers in Physiology, 2020)
Pathogenic variants in KCNQ2 and KCNQ3, paralogous genes encoding Kv7.2 and Kv7.3 voltage-gated K+ channel subunits, are responsible for early‐onset developmental/epileptic disorders characterized by heterogeneous clinical phenotypes ranging from Benign Familial Neonatal Epilepsy (BFNE) to early‐onset developmental and epileptic encephalopathy. KCNQ2 variants account for the majority of pedigrees with BFNE and KCNQ3 variants are responsible for a much smaller subgroup, but the reasons for this imbalance remain unclear. Analysis of additional pedigrees is needed to further clarify the nature of this genetic heterogeneity and to improve prediction of pathogenicity for novel variants. We identified a BFNE family with two siblings and a parent affected. Exome sequencing on samples from both parents and siblings revealed a novel KCNQ3 variant (c.719T>G; p.M240R), segregating in the three affected individuals. The M240 residue is conserved among human Kv7.2-5 and lies between the two arginines (R5 and R6) closest to the intracellular side of the voltage-sensing S4 transmembrane segment. Whole cell patch-clamp recordings in Chinese Hamster Ovary cells revealed that homomeric Kv7.3 M240R channels were not functional, whereas heteromeric channels incorporating Kv7.3 M240R mutant subunits with Kv7.2 and Kv7.3 displayed a depolarizing shift of about 10 mV in activation gating. Molecular modeling results suggested that the M240R substitution preferentially stabilized the resting state and possibly destabilize the activated state of the Kv7.3 subunits, a result consistent with functional data. Exposure to beta-hydroxybutyrate, a ketone body generated during the ketogenic diet, reversed channel dysfunction induced by the M240R variant. In conclusion, we describe the first missense loss-of-function pathogenic variant within the S4 segment of Kv7.3 identified in patients with BFNE. Studied under conditions mimicking heterozygosity, the M240R variant mainly affects the voltage sensitivity, in contrast to previously analyzed Kv7.3 variants that reduce current density. Our pharmacological results provide a rational for the use of ketogenic diet in patients carrying loss-of-function variants in Kv7.2 or Kv7.3 subunits.